“La Surdité Familiale” by Giuseppe Gradenigo 1921 - Martini, Alessandro; Rippa Bonati, Maurizio; Cozza, Andrea; Sorrentino, Flavia (ENT Updates, 2021)
Giuseppe Gradenigo was born in Venice in 1859, and he was a member of the noble Venetian family of the Gradenigo. After graduation in medicine in Padua, he went to Vienna where he deepened his studies in otology and embryology. He obtained, in 1888, the “libera docenza” in otology in Padua, and in 1889, he began to direct the section of otolaryngology of the polyclinic of Turin. After a brilliant career in 1917, he took over the chair of otolaryngology at the University of Naples. Gradenigo was a pioneer in otolaryngology and audiology and a reference figure in the clinical and scientific fields. In this paper, the most important aspects about his works and his biography will be discussed.